The ‘Inevitable’ Women: Studying Female Presence in War Spaces through Tim O’Brien’s The Things They Carried - Barkha (SCHOLARS: Journal of Arts & Humanities, 2023)
The literature of war exposes the gender binaries and stereotypes that are reinforced by war. The Vietnam War is one of the most popular wars in American history; it is the first war televised live. The reason for its popularity lies in its project of ‘re-masculinizing’ America. With the Cold War and the Anti-War protests all over the country, America used the gender norms to justify the war. Of its multi-layered gender role enforcement, first it projects itself as the masculine ‘saviour’ who is going to fight for democracy and rights of a ‘feminized’ Asian country; second, its use of misogynistic slangs to create a homo-social bond among men and alienate women; but can the presence of women be omitted? In my paper I shall do a close textual analysis of The Things They Carried by Tim O’Brien to show how he explores the female presence in the Vietnam War, as well as how the novel is a critique of the war literature of the time that attempts to reinforce the gender binaries.